GUARANTEE OF THE RIGHT TO SILENCE AND OF THE RIGHT NOT TO CONTRIBUTE TO ONE’S OWN INCRIMINATION IN ROMANIAN CRIMINAL PROCEDURE LAW - Domocos, Carmen Adriana (Administrative and Criminal Justice, 2018)
The Romanian legislation establishes in the new penal procedure law the right to silence and the right of non-incrimination of the defendant in the criminal trial.The right to silence (to remain silent) is the implicit procedural guarantee of the right to a fair trial, which results from the case law of the European Court of Justice within the meaning of Article 6 paragraph 1 of the European Convention on Human Rights, according to which judicial authorities cannot oblige a perpetrator (suspected of having committed a criminal offence), a suspect or a defendant to make statements, while having, however, a limited power to draw conclusions against them, from their refusal to make statements.Therefore, the right to silence involves not only the right not to testify against oneself, but also the right of the suspect or defendant not to incriminate oneself. The suspect or defendant cannot be compelled to assist in the production of evidence and cannot be sanctioned for failing to provide certain documents or other evidence. Obligation to testify against personal will, under the constraint of a fine or any other form of coercion constitutes an interference with the negative aspect of the right to freedom of expression which must be necessary in a democratic Romanian society.The right not to contribute to one’s own incrimination (the privilege against self-incrimination) is the implicit procedural guarantee of the right to a fair trial, which results from the case law of the European Court of Justice within the meaning of Article 6 paragraph 1 of the European Convention, according to which judicial bodies or any other state authority cannot oblige a perpetrator (suspected of having committed a criminal offence), a suspect, a defendant or a witness to cooperate by providing evidence which might incriminate him or which could constitute the basis for a new criminal charge. It is essential to clarify certain issues as far as this right is concerned.